Branding - Chiaravalle, Bill; Schenck, Barbara Findlay (--For dummies., 2019)
Discover how brands are created, managed, differentiated, leveraged, and licensed Whether your business is large or small, global or local, this new edition of Branding For Dummies gives you the nuts and bolts to create, improve, and maintain a successful brand. It'll help you define your company's mission, the benefits and features of your products or services, what your customers and prospects already think of your brand, what qualities you want them to associate with your company, and so much more. Packed with plain-English advice and step-by-step instructions, Branding For Dummies covers assembling a top-notch branding team, positioning your brand, handling advertising and promotions, avoiding blunders, and keeping your brand viable, visible, and healthy. Whether you're looking to develop a logo and tagline, manage and protect your brand, launch a brand marketing plan, fix a broken brand, make customers loyal brand champions-or anything in between-Branding For Dummies makes it fast and easy.